2012 IEEE International Conference on Communications (ICC) 2012
DOI: 10.1109/icc.2012.6364448
|View full text |Cite
|
Sign up to set email alerts
|

The influence of meteorological variables on the performance of outdoor wireless local area networks

Abstract: Improving the performance and the behavior of outdoor wireless local area networks (WLAN) is a very important objective for almost all researchers in the telematics field. In this paper, a clear relation between the weather and the performance of an outdoor WLAN is shown. This relation is extracted from a correlation analysis between several meteorological variables and the control and management frames of the data link layer of a WLAN at the Universitat Politècnica de València campus. In order to carry out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…In previous works has been measured the weather's impact on such control frames errors and retransmissions at MAC layer on a real WLAN scenario [11] and in a point-to-multipoint link IEEE 802.11b/g [12]. These researches show a significant correlation between the number of control frame errors and weather conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…In previous works has been measured the weather's impact on such control frames errors and retransmissions at MAC layer on a real WLAN scenario [11] and in a point-to-multipoint link IEEE 802.11b/g [12]. These researches show a significant correlation between the number of control frame errors and weather conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…ITU (International Telecommunications Union) recommendations do not highlight these impartments as significant at the 2.4 GHz frequency range, since SNR is decreased very few dBs. However, it has been shown that despite of so low impact on physical layer, it is really perceived in upper layers as a higher number of lost control frames [4] [5]. Moreover, it is clearly noticed as endusers when we are connected to an outdoor access point under adverse weather conditions.…”
mentioning
confidence: 99%
“…Los trabajos y resultados derivados del estudio presentado en este capítulo, han sido publicados en tres congresos [28], [29] y [31], el último de los cuales está indexado en la lista Core, y una revista [30] indexada en la lista ISI Thomson.…”
Section: Conclusiónunclassified
“…They have been seen at the end of each chapter. Main papers directly related to the research of this thesis have been [28], [29], [30], [31], [32], [33], [34] and [35].…”
Section: Contributionsmentioning
confidence: 99%